Solution Expressions of Discrete Systems of Difference Equations. (30th July 2022) - Elsayed, E. M.; Alofi, B. S.; Khan, Abdul Qadeer
Abstract : In this paper, we obtain the solution forms of fifth order systems of rational difference equations P n + 1 = P n 4 S n 2 Q n / S n − 3 Q n − 1 1 ± P n − 4 S n − 2 Q n, Q n + 1 = Q n − 4 P n − 2 S n / P n − 3 S n − 1 1 ± Q n − 4 P n − 2 S n, and S n + 1 = S n − 4 Q n − 2 P n / Q n − 3 P n − 1 1 ± S n − 4 Q n − 2 P n . Where the initial values are nonzero real numbers. Numerical examples are also provided.